2018
DOI: 10.1142/s0219519418400134
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Parallel-Plate Compression and Finite Element Modeling to Analyze the Mechanical Properties of Intact Porcine Lens

Abstract: The objective of this study is to explore the feasibility of a compression test for measuring mechanical properties of intact eye lenses using novel parallel plate compression equipment to compare the accuracy of implementing a classical Hertzian model and a newly proposed adjusted Hertzian model to calculate Young’s modulus from compression test results using finite element (FE) analysis. Parallel-plate compression tests were performed on porcine lenses. An axisymmetric FE model was developed to simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Currently, assessing the biomechanical properties of the lens is a challenge due to its location inside the eye-globe. Mechanical loading, which is the gold standard for assessing material properties such as Young's modulus, has been utilized for elasticity estimation of the whole lens [8,9]. However, the lens must be removed from the eye-globe, which limits the applicability of mechanical testing for in vivo measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, assessing the biomechanical properties of the lens is a challenge due to its location inside the eye-globe. Mechanical loading, which is the gold standard for assessing material properties such as Young's modulus, has been utilized for elasticity estimation of the whole lens [8,9]. However, the lens must be removed from the eye-globe, which limits the applicability of mechanical testing for in vivo measurements.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a likely underestimation of the elastic modulus in the larger lens biopsy punches and whole lenses due to ellipsoidal geometry potentially dominating instead of cylindrical geometry. This can be partially mitigated by allowing flat plate contact before starting the compression test, but corrections may be better using Hertzian contact theory, and has been demonstrated by other researchers [ 52 ]. It was observed that for biopsy punches below 8 mm the stress–strain curves resembled shapes consistent with linear elastic models rather than Hertzian contact.…”
Section: Discussionmentioning
confidence: 99%
“…These include the seminal work by Fisher [25], who developed the spinning lens method to mimic the lens shape change during accommodation using centrifugal forces. A similar technique was investigated by Burd et al [18], the classical compressional method adopted to characterise the overall lens stiffness [26], stretching of the lens to simulate ciliary muscle forces [27] as well as the indentation [28] and oscillational shear rheometry used on sectioned lens samples [12,13,29]. However, the results revealed by studies adopting the above methods have varied over several orders of magnitude in elastic moduli and inconsistencies in the ageing trends have also been reported [2].…”
Section: Introductionmentioning
confidence: 99%